The Characteristic of Cobalt-Nickel-Iron Alloy Coating Coated on Aluminium, Brass and Stainless Steel - Rozlin N.M Masdek, Nik; Salleh, Zuraidah; Zin Abu, Md; ., . (International Journal of Engineering and Technology, 2018)
Electrodeposition is a well-known and economical method in the coating industry due to its low cost and fast process. This study investigates on the charateristic of electrodeposited Co-Ni-Fe alloy coating coated on three different substrates that is aluminium, brass and stainless steel. The surface morphology, microhardness, surface roughness, and corrosion resistance of Co-Ni-Fe electrodeposited on aluminium, brass and stainless steel was determined. This study compares the different properties of the Co-Ni-Fe alloy coating coated on aluminium, brass and stainless steel which can enhance the mechanical, chemical and corrosion properties of these metals. Aluminium deposited with Co-Ni-Fe alloy coating had the highest microhardness of 427.4 Hv as compared to brass and stainless steel. Meanwhile the surface roughness for all metals deposited with Co-Ni-Fe alloy coating was reduced significantly. In terms of the corrosion behavior, brass coated with Co-Ni-Fe alloy coating has the lowest corrosion rate of 4.699x10-3 mmpy while stainless steel and aluminium had a corrosion rate of 19.82x10-3 mmpy and 66.15x10-3 mmpy, respectively. From the findings it can be seen that microhardness and corrosion resistance showed an increase of about 40% after depositing the aluminium, brass and stainless steel with Co-Ni-Fe alloy coating.Â Â